"There is a presence in anger": An analysis of traditional critiques of racial anger protest - Williges, Flavio (Sofia, 2023)
The article examines a traditional pattern of criticism of racial protests involving what I will call anti-racist rage. These critiques revolve around two basic points: they characterize angry racial protests as gratuitous displays of aggression and emotional lack of control that illustrate irrational, authoritarian, and violent political activism, and as unproductive political strategies. Against this approach, I argue, first, that there are normative reasons for anti-racist anger and that the traditional critique is wrong to ignore these reasons. Second, in light of the objections of irrationality and unproductiveness of the expression of anger, and following Amia Srinivasan’s approach, I argue that even if it does not lead to desired outcomes, even if it is unproductive, the anger present in anti-racist protests is morally justified, and delegitimizing it on instrumental grounds implies acceptance of a kind of affective injustice.